Urea supplementation in rumen and post-rumen for cattle fed a low-quality tropical forage - Oliveira, Cristhiane Viol Ribeiro de (2020)
The aim of this study was to evaluated differences between the supplementation or infusion of urea in rumen and/or abomasum on forage digestion, nitrogen (N) metabolism, urea kinetics and urea transporters in heifers fed a low-quality tropical forage. Five heifers (283±23 kg, Body Weight, BW) were fitted with rumen and abomasum fistulas and assigned to a 5 ×5 Latin square design. The treatments were: control (only forage), continuous infusion of urea in the abomasum (AC), continuous infusion of urea in the rumen (RC), a pulse dose of urea in the rumen every 12 hours (PR), and a combination of PR and AC, with half of the urea dose delivery in each supplementation site (PRAC). General, treatments did not influence (P>0.10) forage intake and fiber digestion. The ruminal ammoniacal nitrogen concentration was higher (P<0.10) when urea was totally or partially supplied in the rumen. The control exhibited the lowest (P<0.10) fecal and urinary N losses, which were, overall, increased by supplementation. The highest urinary N losses (P<0.10) was observed when urea was either totally or partially supplied as a ruminal pulse dose. The rumen N balance was negative for the control and when urea was totally supplied in the abomasum. The greatest microbial N production (P<0.10) was obtained when urea was partially or totally supplied in the abomasum. The highest efficiency of microbial production (EFM) was observed (P<0.10) when urea was partially or totally supplied in the abomasum, and the lowest EFM (P<0.10) occurred for the control. The amount of urea recycled to the gastrointestinal tract was increased (P<0.10) by providing urea. The amount of N-urea returned to the ornithine cycle was increased (P<0.10) by supplemental urea and did not differ (P>0.10) amongst supplementation forms. The greatest (P<0.10) amounts of N-urea used for anabolism was observed when urea was totally and continuously infused in the abomasum. The continuous abomasal infusion of urea caused the highest (P<0.10) assimilation of microbial N from recycling, whereas the remaining treatments did not differ (P>0.10) to each other. The serum urea N (SUN) was higher (P<0.10) and the blood 3-methyl histidine was lower (P<0.10) when supplemental urea was provided compared to the control. The blood activity of aspartate transaminase and alanine transaminase was higher (P<0.10) when urea was totally supplied as a ruminal pulse dose. The genes associated with aquaporin 3 and urea transport protein UT-B were more expressed (P<0.10) in the control compared to the supplemented treatments. The continuous releasing of urea along the day either in the rumen or abomasum, is able to improved N accretion in the animal body, despite of mechanism responsible for that be different. The supply of urea as a pulse dose in the rumen is not able to confer the same benefits, probably because a greater amount of N is lost in the urine. Current technologies for delaying urea releasing in the rumen are not totally effective in terms of achieving a steady state condition. Therefore, the protection of urea aiming to its releasing into a post-rumen compartment seems a promising technology that may improve the N utilization from a non-edible N source. Keywords: Non-protein nitrogen. Ruminant. Supplementation.